Study of pulmonary tuberculosis in diabetes mellitus - A., Vinay Kumar; K., Raj Kumar; Reddy R., Nithin Kumar (International Journal of Research in Medical Sciences, 2018)
Background: To study the clinical profile of pulmonary tuberculosis in diabetic patients and to study the radiographic patterns of pulmonary tuberculosis in diabetic patients. Methods: The study was undertaken on 100 patients with diabetes mellitus and pulmonary tuberculosis of both sexes admitted to Chalmeda Anand Rao Institute of Medical Sciences, Bommakal, Karimnagar. Results: The fasting blood sugar value showed a definite co-relation with pulmonary tuberculosis. 41% of the patients had fasting blood sugar value between 201 to 300mg/dl and 30% had value between 151-200mg/dl and 23% of the patients had value above 300mg/dl. Mean fasting blood sugar value was 234.4mg/dl. Right sided lung lesions were noted in 37% of the cases and left sided lesions in 33% of the cases. Upper lobe lesions were noted in 68% of the cases and bilateral lesion in 30% of the study group. Conclusions: Uncontrolled diabetes mellitus patients are more prone to develop pulmonary tuberculosis compared to non diabetics. Sputum examination tends to be positive in diabetics compared to non diabetics.